Hukum Pemanfaatan Tanoh Gala Menurut Fikih Syafiiyah - Haikal, Muhammad (Al Mabhats : Jurnal Penelitian Sosial Agama, 2018)
Mortgage land is land that is used by the pawner (rahin) as collateral (marhun) to the person who receives (murtahin). Many Acehnese use such pawn land, where this action makes it difficult for Rahin to pay for it. Throughout this problem, the scientific question arises upon how the law of mortgage land utilisation according to fiqh Syafiiyah ?. The method used in this study is qualitative with a research library approach. The results showed that it was forbidden to use the mortgage land by marhun and it may use by rahin.